Measuring Auxin Transport Capacity in Seedling Roots of Medicago truncatula - Jason Ng; Ulrike Mathesius (Bio-Protocol, 2016)
Measurement of auxin transport capacity provides quantitative data on the physiological machinery involved in auxin transport within plants. This technique is easy to perform and gives quick results. Radiolabelled auxin (indole-3-acetic-acid) is fed into the roots of Medicago truncatula via an agar block. The resulting radioactivity from radiolabelled auxin uptake in the roots is measured with a liquid scintillation counter. Here, we describe the measurement of auxin transport capacity around the nodulation susceptible zone in young seedling roots of M. truncatula in response to rhizobia inoculation. Similar assays could be adapted in other plant species and to answer other biological questions.